JUDUL IMPLEMENTASI SEMINAR MICROSOFT WORD UNTUK MENINGKATKAN LITERASI DIGITAL SISWA SMP 3 IBRAHIMY SUKOREJO - Muyessiroh; Wiwik Handayani; Zaehol Fatah (Jurnal Padamu Negeri, 2025)
This study aims to describe how to organize a seminar on Microsoft Word as an effort to improve digital literacy skills among students of SMP 3 Ibrahimy. Digital literacy is an important skill needed by students in facing challenges in the era of information technology. This study uses a qualitative descriptive method, by collecting data through observation, interviews, and documentation during the seminar. The results of the study indicate that the Microsoft Word seminar succeeded in improving students' understanding of the basic and advanced functions of this word processing software. Students became more proficient in creating documents, organizing text formats, and utilizing features that help their learning tasks. In addition, this activity also encouraged a positive attitude towards the use of technology in a beneficial way